EPISTEMOLOGI KECERDASAN BUATAN (AI) DAN PENTINGNYA ILMU ETIKA DALAM PENDIDIKAN INTERDISIPLINER - Michael Reskiantio Pabubung (Undiksha, 2021)
Artificial intelligence (AI) is an “umbrella term” used to describe simulations carried out by machines or devices, which are connected to an ocean of data, which resembles human intelligence. There is no doubt that AI has had a positive impact on many aspects of human life: economy, education, government, defense, and security. However, AI is like two sides of a coin which also has negative impacts. The multidimensional impacts caused by AI lead to a question about how to keep pace with AI progress while staying through the desired path. To answer this question, philosophy always begins with an epistemological analysis. By departing from facts and epistemological analysis about AI, the author came to believe in the importance of the role of interdisciplinary education. By using qualitative methods through literature analysis on AI as a material object, and philosophy, especially epistemology as a formal object, this essay offers the importance of AI and Ethics as a compounded lecture material in the era and disruption of AI. As a time-responsive educational institution, every university needs to consider the necessity for lecture materials on the basics of AI and Ethics for every student.